Higher Education and Dilemmas of Deinstitutionalization - Martin, Christopher; Pulvermacher, Andrew (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
The pandemic has made the mass remote delivery of higher education more plausible as a general direction for growth in the long-term. Choosing between this general direction and the status quo introduces various ethical dilemmas having to do with the basic aims and values of higher education. A move to remote learning as the institutional norm may set back some of these aims and values while advancing others. However, we also argue that complicating the assessment of these dilemmas is epistemic uncertainty about the traditional (i.e., late-twentieth-century) institutional context and what makes that context educationally worthwhile. Addressing these dilemmas requires a better understanding of what an educational institution is as well as those respects in which it adds value to society’s educational projects.